Pengaruh Mekanisme Good Corporate Governance dan Kinerja Keuangan Terhadap Pelaporan Pengungkapan Keberlanjutan - Yudhanti, Ashari Lintang; Listianto, Ela (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2021)
Abstract This research is based on the many problems that occur caused by mining companies that are still lacking in economic, environmental, and social responsibility resulting from the company's activities. This research uses a quantitative approach method. The observation period 2018-2020 using secondary data taken from the official website of the Indonesia Stock Exchange and the official website of the mining company that was used as the research sample. This research shows that only liquidity has an effect on sustainability report, while audit committee, managerial ownership, independent commissioner, board of commissioners, board of directors and profitability have no effect on sustainability report.